The Impacts of Corporate Governance on Dividend Payout Ratio Policy Before and During the Covid-19 Era: The Study Case in the Energy Industry in Indonesia - Kazia Laturette; Wendra Hartono; Kartikasari Gunawan (AIBPM Publisher, 2023)
This study aims to analyze the impacts of good corporate Governance during the Covid -19 era on Indonesia's dividend payout ratio policy. Moreover, during the Covid-19 era, higher management such US boards of Directors have been urged to deal with all difficulties and uncertainties in the business situation. During the Covid-19 era, energy has faced big challenges due to lockdown policy in many big areas, leading to disruptive global economic supply chains. Due to the lockdown, the number of energy demands has decreased. Henceforth, the price is becoming more expensive. This research will show and compare the conditions of the energy industry before and during the Covid-19 Pandemic. This research is categorized quantitative research which the sample obtained from the secondary data, financial reports, from basic material industry for publicly listed companies on the Indonesia Stock Exchange during 2018 – 2020, a total of 33 companies. The study showed that only the boards of Directors and Commissioners Independent before the Pandemic affected the dividends payout ratio.